2000
DOI: 10.1243/0954406001523731
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical fatigue characterization of zirconia (8%Y2O3-ZrO2) and mullite thermal barrier coatings on diesel engine components: Effect of coatings on engine performance

Abstract: 8%Y 2 O 3 -stabilized zirconia (8YPSZ) and mullite (3Al 2 O 3 Á2SiO 2 ) powders, which were made plasma sprayable by using an organic binder (polyvinyl alcohol), have been plasma spray coated on to the piston head, valves and cylinder head of a 3.8 kW single-cylinder diesel engine, previously coated with Ni±Cr±Al±Y bond coat. The engine with components coated with 250 mm thick 8YPSZ and 1 mm thick mullite thermal barrier coatings has been evaluated for fuel eciency and for endurance during 500 h long rigorous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…men appeared to be glassy (Fig. 2c), as has also been observed by Ramaswamy et al 2 This result was confirmed using XRD (see Fig. 3).…”
Section: As-sprayed Microstructuresupporting
confidence: 87%
See 2 more Smart Citations
“…men appeared to be glassy (Fig. 2c), as has also been observed by Ramaswamy et al 2 This result was confirmed using XRD (see Fig. 3).…”
Section: As-sprayed Microstructuresupporting
confidence: 87%
“…[1][2][3][4][5][6][7][8][9] Many TBC systems consist of a ceramic topcoat plasma-sprayed onto an intermetallic bond coat attached to a superalloy substrate. yttriastabilized zirconia (7 wt.% Y 2 O 3 -ZrO 2 or YSZ) is commonly used as the ceramic topcoat in these systems because of its high melting temperature (∼2700 • C) and low thermal conductivity (∼2 W/m/K).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal barrier coatings (TBCs) have been a topic of great scientific interest worldwide for several decades. They have been used for engine components in turbine and aircraft engines in order to achieve improved engine performance and fuel efficiency by increasing the actual temperature of engine operation [4].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Alternative to these coatings that may show enhanced toughness as happens in bulk composites 9,10 are thermal sprayed mullite/ZrO 2 coatings. Surprisingly, there are few works devoted to these coatings [11][12][13][14] and most of them are produced by plasma spraying the Al 2 O 3 -ZrSiO 4 stoichiometric mixture, which ideally reacts to form a composite of mullite (33.4 mol %) and ZrO 2 (66.6 mol %) phases.…”
Section: Introductionmentioning
confidence: 99%